"Pseudoclusters" and typing by random amplification of polymorphic DNA of Aspergillus fumigatus. Issue 2 (February 1995) - Loudon, K W; Coke, A P; Burnie, J P
Abstract : This short report serves as a warning to the unwary of possible "pseudoclusters" of infection with Aspergillus fumigatus as shown by the typing system, random amplification of polymorphic DNA (RAPD). This was demonstrated by typing 10 epidemiologically distinct isolates of A fumigatus using two different preparations of Taq DNA polymerase. One of the enzymes did not discriminate between the isolates, giving the false impression that a cluster of infection had occurred. Enzyme source is thus a key variable when using RAPD to distinguish between isolates of A fumigatus.